EXPERIMENTAL NON-ALCOHOLIC FATTY LIVER DISEASE INDUCED BY HIGH-CHOLESTEROL DIET - Migliorini, Maíza Pellissari; dos Santos, Gabriel; Matera, Maysa Ortolani; Wenglarek, Karyn Maria; da Silva, Thais de Lima; Parlow, Jaqueline Meert; Justus, Isabela Hess; Colmenero, Flávia Cristina; Dreweck, Marcelo de Oliveira; Ioshii, Sérgio Ossamu; Sturzeneker, Mário Cláudio Soares (Seven Editora, 2025)
Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in adults. It is often associated with metabolic syndrome, obesity, type 2 diabetes, and cardiovascular disease (CVD), especially atherosclerotic CVD, which is closely related to cholesterol levels. The recommended daily cholesterol intake should be < 300 mg. However, the contemporary diet is marked by the high consumption of foods rich in cholesterol and saturated fats. In this context, animal models with natural disease induction, based on risk factors, mimicking contemporary dietary patterns, play a fundamental role. In this line, we carried out the present experiment, using 12 Wistar rats divided into 3 groups: basal control (GB), normal control (NG) and cholesterol (CG). GB was sacrificed at baseline to achieve normal baseline parameters. The NG received a standard diet and the CG received a diet rich in cholesterol, from baseline to the end of the study, when blood and liver tissue samples were collected for the preparation of slides, which were analyzed blindly, under the criteria of the scoring system for histological evaluation of NAFLD. All animals in the CG developed steatosis and balloonization in their highest scores, Moderate lobular inflammation occurred in 75% and mild in 25% of the group. Scores compatible with the presence of nonalcoholic steatohepatitis (NASH) were observed throughout the CG. It is concluded that there was the development of experimental NAFLD in Wistar rats and, based on the activity score, there was the development of NASH. DOI: https://doi.org/10.56238/sevened2025.021-007